2020
DOI: 10.32674/jis.v10i2.616
|View full text |Cite
|
Sign up to set email alerts
|

The Predicting Effects of Self-Efficacy, Self-Esteem and Prior Travel Experience on Sociocultural Adaptation Among International Students

Abstract: Personal and situational factors contribute to international students’ sociocultural adjustment in a host society. Thus this study attempts to determine the roles of self-efficacy, self-esteem, and previous travel experience on sociocultural adjustment. The sample for this study constituted 328 undergraduate and postgraduate international students, studying in three Chinese universities. Participants completed a set of tests measuring their sociocultural adjustment, self-efficacy and self-esteem, as well as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
0
10
0
2
Order By: Relevance
“…Typically, however, these scholars highlight international students' language abilities or students' confidence in English as predictive of success (Lopez & Bui, 2014). Other scholars have considered the importance of self-efficacy (Gebregergis et al, 2020). Wang, et al, (2018) suggest that self-efficacy is an index of motivation and achievement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, however, these scholars highlight international students' language abilities or students' confidence in English as predictive of success (Lopez & Bui, 2014). Other scholars have considered the importance of self-efficacy (Gebregergis et al, 2020). Wang, et al, (2018) suggest that self-efficacy is an index of motivation and achievement.…”
Section: Discussionmentioning
confidence: 99%
“…Confidence, then, refers to a level of assurance in one's capacities (as opposed to abilities), judgments, and qualities (Bandura, 1977). The concept of self-confidence is much more difficult to evaluate because it is focused on the future based on the past, rather than one's efficacy or esteem in the present (Gebregergis, Mehari, Gebretinsae,& Tesfamariam, 2020). However, the well-documented positive relationship between academic self-confidence and academic success among international and other populations in universities and colleges (Lemoyne et al, 2017;Shoemaker, 2010;Stankov et al, 2012;Telbis et al, 2014;Wang et al, 2018) warrants the examination of the role of academic self-confidence on thriving among international college students.…”
Section: Confidencementioning
confidence: 99%
“…Regional multiculturalism determines the transformation of value-oriented and content-technological foundations for work with international students (Aldakimova, 2019). (Anikina, 2018;Beregovaya et al, 2020;Fedosov, 2015;Ivanova et al, 2018;Mukha et al, 2018) and foreign (Gebregergis et al, 2020;Khanal & Gaulee, 2019;Presbitero, 2016) science has been sufficiently and comprehensively studying the features, types of adaptation of international students, various barriers determining the objective need to develop a system of comprehensive support for students from foreign countries in each university.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-cultural adaptation is defined as the focus of individuals on creating and maintaining a relatively stable system of relationships with a new socio-cultural environment for successful socialization and life (Kim & Kim, 2016). The studies revealed that the success of socio-cultural adaptation of international students is influenced not only by self-effectiveness and self-esteem, but also by the previous experience of student tourist trips (Gebregergis et al, 2020).…”
mentioning
confidence: 99%
“…It is beneficial for host universities to enroll international students on their study programs, as this would enable them to ensure further prosperous growth. Incoming students not only enrich intellectual and cultural campus environment, but also bring substantial revenue to national economy, making education one of the most profitable service segments (Gebregergis et al, 2020).…”
Section: Introductionmentioning
confidence: 99%